Cloning and expression of three heat shock protein genes in the gills of Cherax quadricarinatus responding to bacterial challenge. (May 2020) - Wang, Qiong; Huang, Chunmei; Liu, Ke; Lu, Min; Dan, Solomon Felix; Xu, Youhou; Xu, Yixue; Zhu, Peng; Pan, Hongping
Abstract: Cherax quadricarinatus is seriously affected by multiple types of pathogens, including bacteria and viruses, and has been widely transplanted around the world. Heat shock proteins (Hsps) are a group of molecular chaperones that play important roles in promoting the proper refolding and blocking the aggregation of denatured proteins. In this study, CqHsp60, CqHsp70 and CqHsp90 from C. quadricarinatus were cloned, and their expression patterns were analysed. The CDS (coding sequence) lengths of the CqHsp60, CqHsp70 and CqHsp90 genes were 1731 bp, 1932 bp and 2199 bp, encoding 576, 643 and 732 amino acids, respectively. CqHsp60 was 99.13%, 98.78% and 88.63% identical to the corresponding sequences of Cherax cainii, Cherax destructor and Eriocheir sinensis, respectively. CqHsp70 showed 99.84%, 92.73% and 91.58% identity to the corresponding sequences of C. cainii, C. destructor and E. sinensis, while CqHsp90 was 98.25%, 98.51% and 91.41% identical with those of C. cainii, C. destructor and E. sinensis, respectively. The expression patterns of the three CqHsps were different between males and females. CqHsp60 and CqHsp70 exhibited the highest expression in the hepatopancreas of males and the gonads of females, and CqHsp90 presented the highest expression in the gonads of males and hepatopancreas of females. After pathogenic inoculation, the death trend of C. quadricarinatus at different time points was the same in association with different pathogens, with most deaths occurring within 6 h post-inoculation. The trend of CqHsp transcription at different time points was the same among the groups treated with Vibrio alginolyticus, Vibrio parahemolyticus and Aeromonas hydrophila, exhibiting upregulation first and then downregulation. The expression of CqHsp60 and CqHsp70 in the gills of living C. quadricarinatus was less than 3.5 times that in the PBS group, but in the gills of dead C. quadricarinatus under A. hydrophila inoculation, its expression was more than 5–9 times that in the PBS group. CqHsp90 expression changed dramatically in the V. alginolyticus, V. parahemolyticus and A. hydrophila groups, in which it exceeded 50 times the level in the PBS group. These results indicated that CqHsps could induce the activation of the immune system within a short time and that CqHsp90 could be used as a more effective molecular biomarker than CqHsp70 and CqHsp60 in a pathogenic bacterium-polluted environment. Highlights: Hsp60, Hsp70 and Hsp90 were cloned from Cherax quadricarinatus. Hsp60, Hsp70 and Hsp90 were constitutively expressed in various tissues of Cherax quadricarinatus. CqHsp90 is a more effective molecular biomarker than CqHsp70 and CqHsp60 in a pathogenic bacterium-polluted environment.